Study the effects of Cadmium Chloride on some organs tissues of female Albinus Rat - Ø§Ù„ÙØªÙ„Ø§ÙˆÙŠØ¸Ø§ÙØ±Ø© Ø¬Ø¹ÙØ± Ø¹Ø¨Ø¯ Ø¹Ù„ÙŠ; Ø§Ù„Ø´Ø¨Ù„ÙŠÙƒØ±Ø§Ø± Ø³Ù„ÙŠÙ… Ø²Ø§ÙŠØ¯ (Al-Qadisiyah Journal of Pure Science, 2017)
The current study was carried out in the animal house of the College of Medicine in University of Kufa. It was conducted also in the laboratories of histopathology and biochemistry in Al-sadir Educational Hospital and Higher Education laboratory in the College of Education for girls / Kufa University, during the period 25/10/2008 – 19/3/2009. It was designed to demonstrate the influence of acute dose of Cadmium Chloride (75mg/kg) and oral subchronic administration in /L with drinking water for the periods (3,6,9) weeks2mg CdCl) 10,20,30(duodenum , liver and kidney tissues of female albinus rat . Acute and subchronic administrations demonstrates hypertrophy in the striated columnar epithelial cells covering the villi of duodenum and enlarged paneth cells of intestinal glands with vacuolated cytoplasm. Similar changes occur in subchronic administration ranged between mild to moderate and some times severe when dosing level and duration are elevated. The result of acute administration in liver tissue demonstrates hypertrophy, necrosis, elongated and enlarged cells in different areas of liver tissues, also appears interstitial infiltration in portal triad region and hyperaemia in some of the sinusoids with kupffer cell. The result of subchronic administration had similar changes ranging between : mild, moderate and severe sometimes to those in acute administration with blurring of radiated structure of liver cells cords. Acute administration of kidney tissue reveals hyperaemia, enlargment, swelling, shrinkage in some glomeruli in the cortex, while in proximal tubules there appear cell hypertrophy and necrosis. Moreover, one or two regions of medulla demonstrate hyperaemia and cell casts in the lumen of renal tubules. Subchronic effects range between mild to moderate and rarely severe when dosing level and duration are elevated, it is sometimes noticed that in the same section there are shrinkage of glomeruli and expansion of capsule, hypertrophy, hyperaemia and necrosis of proximal tubules, alienation epithelial cell and diffusion of inflammatory cell, while medulla show hypertrophy and necrosis of epithelial cell and interstitial tissues fibrosis.